HBR's 10 must reads on managing across cultures (Harvard Business Review Press, 2016)
This book will inspire you to: Develop your cultural intelligence. Overcome conflict on a team where cultural norms differ. Adopt a common language for more efficient communication. Use the diverse perspectives of your employees to find new business opportunities. Take varying cultural practices into account when resolving ethical issues. Accommodate and plan for your expatriate employees.